Low Energy Extracorporeal Shockwave Therapy for the Treatment of Myositis Ossificans in a Case of Cerebro Vascular Accident - Sarkar, Bibhuti; Rau, S S (Indian journal of physiotherapy and occupational therapy, 2013)
A 40 year old male Cerebro Vascular Accident (CVA) patient with right hemiplegia was treated with low energy extracorporeal shockwave therapy (ESWT) for myositis ossificans at right hip and right elbow. After six sitting of low energy ESWT along with other remedial exercises it was observed that the restricted ROM at his right hip and elbow were improved. The functional ability of the patient was also improved. The finding of this case report encouraged us to conclude that low energy ESWT combined to a correct rehabilitation therapy can be a modality of choice for the treatment of myositis ossificans.